Analysis of the Influence of the Technology Acceptance Model (TAM) on the Intention to use Tthe Payment Features of Kaipay - Alrosa Anindita Fairus; Nanda Ahda Imron; Sapto Priyanto; Surya Aji Ermanto (Pusat Penelitian dan Pengabdian Masyarakat Poltrada Bali, 2022)
Technology development affects some companies by creating innovations to increase corporate activity. PT Kereta Api Indonesia (Persero) participates in the development of innovations that support customer comfort. Innovation lies in the developing of the KAI Access application. Not only that, PT Kereta Api Indonesia (Persero) also further developing the application by presenting the KAIPay payment feature. Researchers used the Technology Acceptance Model (TAM) to analyze KAI Access application users intention towards KAIPay payment feature. . The method used is a structural equation model (SEM) based on partial least square (PLS), along with a data collection method using Google Forms. The data analysis technique was performed using the SmartPLS application. The conclusions from the results of this study show that of the 7 hypotheses proposed, 6 hypotheses can be accepted and 1 hypotheses was rejected.